Sand tides : a concept design exploration of colonial possibilities through gameplay and spatial inequality : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design, Massey University College of Creative Arts, Wellington, New Zealand - Sheppard, Carter Hayden (Massey University, 2019)
Representations of off-world colonisation in science fiction often propagate popularised and uncritical attitudes towards how communities and institutions engage in the practice of colonisation. The themes of adventure, freedom and exploration, permeates colonial era propaganda and the national mythos of colonial nations. The mass appeal of adventure, freedom and exploration in video games has simplified the way colonisation is portrayed in video game franchises. The power of colonial institutions, cultural attitudes and how communities respond to unique spatial limitations have unforeseen consequences on communities within the influence of colonial regimes. Concept design can create new opportunities for layered engagement towards a new, science fiction video game Intellectual Property (IP), where players create emergent narratives about the relationship between colonisation and the regulation of space. This research proposes a conceptual design investigation to reconcile the mass appeal of colonisation in science fiction influenced video games with the historical outcomes and origins of colonisation. This will be explored through the production and presentation of vehicle designs for an original, science fiction genre, video game property which will demonstrate a synthesis between the properties' in-game mechanics and its commentary on off-world colonisation lore and world-building which are grounded in historical analysis.
Some possibly copyrighted Figures are retained for the purpose of criticism or review under the "Fair Use" principle.
Keywords: Colonial history; spatial inequality; science fiction; concept design; cutaway illustration; video games; 330316 Visual communication design (incl. graphic design)